2015
DOI: 10.1111/cogs.12228
|View full text |Cite
|
Sign up to set email alerts
|

A Multiple‐Channel Model of Task‐Dependent Ambiguity Resolution in Sentence Comprehension

Abstract: Traxler, Pickering, and Clifton (1998) found that ambiguous sentences are read faster than their unambiguous counterparts. This so-called ambiguity advantage has presented a major challenge to classical theories of human sentence comprehension (parsing) because its most prominent explanation, in the form of the unrestricted race model (URM), assumes that parsing is non-deterministic. Recently, Swets, Desmet, Clifton, and Ferreira (2008) have challenged the URM. They argue that readers strategically underspecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 45 publications
2
51
0
Order By: Relevance
“…For example, in recent work Caplan, Michaud, and Hufford (2013) have investigated 61 persons with aphasia on different syntactic structures and different tasks (sentence-picture matching, sentence-picture matching with auditory moving window presentation, and object manipulation). Based on this large dataset, they concluded that the underlying deficit may be a reduction in processing resources; they also found an interaction between task demands and parsing difficulty (a topic that is of great interest in unimpaired sentence processing; see Loga cev & Vasishth, 2015;P. Loga cev and S. Vasishth (2014), unpublished data.…”
Section: Discussionmentioning
confidence: 97%
“…For example, in recent work Caplan, Michaud, and Hufford (2013) have investigated 61 persons with aphasia on different syntactic structures and different tasks (sentence-picture matching, sentence-picture matching with auditory moving window presentation, and object manipulation). Based on this large dataset, they concluded that the underlying deficit may be a reduction in processing resources; they also found an interaction between task demands and parsing difficulty (a topic that is of great interest in unimpaired sentence processing; see Loga cev & Vasishth, 2015;P. Loga cev and S. Vasishth (2014), unpublished data.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the activation-based model may be able to account for Logačev and Vasishth's (2016) observation that the parser seems to behave in a way that resembles a race between interpretations (low attachment vs. high attachment) but it is also taskdependent (as assumed by Swets et al, 2008). This could be achieved by setting the timeout (the parameters of the accumulator associated with the retrieval failure) to be task-dependent: longer timeouts when instructions or context encourage attentive reading and shorter timeouts when a full interpretation is not needed for successfully completing the experimental task.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, for the activation based-model with different variances, the relationship between reading times at the different conditions would depend on comprehension accuracy. Future work that includes measures of reading times and queries for the comprehension of the relative clause, as well as manipulates task demands could compare the activation-based model with different variances, the direct-access model, and the model presented in Logačev and Vasishth (2016), which subsumes the unrestricted race model and allows it to be task-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research has shown that syntactic ambiguity does not necessarily slow down comprehension (e.g., Logačev & Vasishth, 2016;Swets, Desmet, Clifton, & Ferreira, 2008;Traxler, Pickering, & Clifton, 1998;Van Gompel, Pickering & Traxler, 2000).…”
Section: Violations Of Gricean Maximsmentioning
confidence: 99%